Search engine and their implications for aspects of privacy - Affonso, Elaine Parra; Monteiro, Silvana Drumond; Vidotti, Silvana Aparecida Borsetti Gregorio; Goncalves Sant'Ana, Ricardo Cesar [UNESP] (Univ Brasilia, Dept Ciencia Informacao, 2017)
Search engines use strategies to deal with information overload and in so doing, they provide more efficient results, such as personal search, which by collecting multiple data from participants can involve threats to privacy. The goal on this project is to explain privacy issues by evaluating aspects of awareness and user's control on the process of data collection by search engines. An exploratory investigation was conducted in Google's and Bing's privacy policies to identify possible data collected by such mechanisms. Data were grouped in categories and analyzed about mention in policies and to the possibility of user's control. It may be highlighted that mention of data collection specifically by search engine is scantily evidenced. Further, although control possibility exists, a thorough interpretation of privacy policies and configuration must be done so that the user may be aware of the process. In conclusion, the privacy-benefit dyad may be a burden in control issues on data collection and the search for relevance in results may be above the right to privacy, this is because when users control their configurations and restrict data collection, they make results less relevant, and when customizing, they open access ports to their data.
Keywords: Bing; Google; Search engine; Personal search; Privacy